Fabrication of AA6061/Al2O3p composites from elemental and alloy powders - Lee, KB; Sim, HS; Kim, YS; Han, JH; Kwon, H (KLUWER ACADEMIC PUBL, 2002)
The tensile properties and microstructures of AA6061/Al(2)O(3)p composites fabricated by the pressureless infiltration method under a nitrogen atmosphere were examined. Since the spontaneous infiltration of molten metal into elemental powders bed as well as alloy powders bed occurred at 700degreesC for 1 hour under a nitrogen atmosphere, it was possible to fabricate 6061 Al matrix composite reinforced with Al(2)O(3)p irrespective of the type of metal powders. Both MgAl2O4 and MgO were formed at interfaces between Al2O3 and the matrix. In addition, MgAl2O4 was formed at within the matrix by in situ reaction during composite fabrication. Fine AlN was formed by in situ reaction in both composites. A significant strengthening in the composites occurred due to the formation ofin situ AlN particle and addition of Al2O3 particles, as compared to the commercial alloy, while tensile properties in the both elemental and alloy powders composites showed similar trend. (C) 2002 Kluwer Academic Publishers.
Keywords: METAL-MATRIX COMPOSITES; PRESSURELESS INFILTRATION TECHNIQUE; MICROSTRUCTURAL DEVELOPMENT; TECHNOLOGIES; INTERFACES